FRI0110 Assessment of Immunogenicity of Live Zoster Vaccination in Rheumatoid Arthritis Patients on Background Methotrexate before and after Initiating Tofacitinib or Placebo. (15th July 2016) - Winthrop, K.; Wouters, A.; Choy, E.; Soma, K.; Hodge, J.; Nduaka, C.; Biswas, P.; McNeil, L.; Passador, S.; Mojcik, C.; Rigby, W.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. Clinical guidelines recommend live zoster vaccine (LZV) to prevent shingles in RA, but this has not been studied in RA patients (pts) and the effect of tofacitinib on humoral or cell-mediated responses to LZV is unknown. Objectives: To evaluate the effect of tofacitinib upon the immune response (IR) and safety of LZV. Methods: Pts were aged ≥50 years with active RA (≥4 tender/painful joints and ≥4 swollen joints) despite methotrexate (MTX) ≥4 months (15–25 mg/wk before screening) (study NCT02147587 ). Pts with prior history of zoster vaccination were excluded, as were those receiving any vaccine in the 6 wks prior to randomisation. After screening, eligible pts on background MTX received LZV and then either tofacitinib 5 mg BID or placebo (PBO) starting 2–3 wks post-vaccination. Both humoral (varicella-zoster virus [VZV]-specific IgG via gpELISA) and cell-mediated responses (VZV-specific T cell enumeration via ELISPOT) before vaccination (baseline [BL], day of vaccination), and then at 2, 6 and 14 wks post-vaccination were measured. Primary endpoint: geometric mean fold rise (GMFR) in VZV-specific IgG titre at 6 wks post-vaccination. Secondary endpoint: proportion of pts achieving a ≥1.5 fold rise in VZV-specific IgG titre 6 wks post-vaccination. Exploratory endpoint: GMFR in VZV-specific T cells (spot-forming cells/10 6 peripheral blood mononuclear cells) by ELISPOT between BL and 6 wks post-vaccination. Pts were followed for 12 wks after randomisation for safety. Results: 112 pts were randomised to PBO (n=57) and tofacitinib (n=55). Most PBO (93%) and tofacitinib (98%) pts were evaluable for IR endpoints. Pts were similar with regard to sex, age, baseline disease activity and baseline VZV immune measures (i.e. IgG, ELISPOT). The GMFR in VZV-specific IgG titre at 6 wks was 2.11 for tofacitinib and 1.74 for PBO. GMFRs in tofacitinib and PBO pts were comparable with GMFRs in healthy people ≥50 years as indicated in the LZV labels. The proportion of pts with a 1.5 fold rise in IgG titre at 6 wks post-vaccination rise trended higher for tofacitinib (57.4%) vs PBO (43.4%). The VZV-specific T cell GMFR at 6 wks increased similarly for tofacitinib (1.50) and PBO (1.29). SAEs occurred in 0 and 3 (5.5%) of PBO and tofacitinib arms respectively. One pt had cutaneous dissemination with vaccine-strain VZV (Oka strain virus) 2 days after starting tofacitinib (16 days post-vaccination). This pt was found to lack pre-existing immunity to VZV, consistent with vaccine-induced disease. The event resolved after tofacitinib discontinuation and antiviral therapy. Conclusions: Pts starting tofacitinib had similar VZV-specific humoral and cell-mediated IRs to LZV as compared to PBO-treated pts. Vaccination appeared safe in pts subsequently treated with tofacitinib; however, one patient who lacked pre-existing VZV immunity developed vaccine-induced disease. Acknowledgement: Previously presented (Winthrop K et al. Arthritis Rheumatol 2015; 67 (S10): Abstr 12L) and reproduced with permission. This study was funded by Pfizer Inc. Editorial support was provided by S. Johnson of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: K. Winthrop Grant/research support from: BMS, Pfizer Inc, Consultant for: Pfizer Inc, UCB, AbbVie, Lilly, BMS, Galapagos, and Amgen, A. Wouters Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Choy Grant/research support from: Amgen, Boehringer Ingelheim, Chugai Pharma, Ferring Pharmaceuticals, Novimmune, Pfizer Inc, Roche, and UCB, Speakers bureau: Amgen, Boehringer Ingelheim, Chugai Pharma, Eli Lilly, Hospira, MSD, Novartis, Pfizer Inc, Regeneron, Roche, Sanofi-Aventis, and UCB, K. Soma Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Hodge Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, P. Biswas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. McNeil Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Passador Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Mojcik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, W. Rigby Grant/research support from: Amgen, Pfizer Inc and Roche., Consultant for: for Bristol-Myers Squibb, Eli Lilly, Pfizer Inc and Roche